Análisis descriptivo del Currículo de formación del docente de Matemáticas, frente al Currículo del Educación General Básica - Ocaña Tapia, Nancy Patricia (2023)
The present research paper entitled "Descriptive Analysis of the Mathematics Teacher Training Curriculum, Versus the General Higher Basic Education Curriculum", analyzes the curriculum of the teaching of Mathematics developed in the career of Pedagogy of Experimental Sciences: Mathematics and Physics of the National University of Chimborazo (UNACH), compared to the curricular contents established in the Higher General Basic Education (EGBS) of the Ministry of Education of Ecuador; an observation sheet was used for this analysis in order to compare the contents of the two curricula of analysis in the field of mathematics, therefore, this research in seeking the percentage similarity has a quantitative approach and by not manipulating variables has a nonexperimental design of descriptive level. The population of analysis is established by the number of contents of the Mathematics curriculum of both General Higher Basic Education and career. Finally, the results showed that there is a 98% similarity between the contents of the analyzed curricula, plus, there is a 2% of contents that are only addressed in the career of Pedagogy of Experimental Sciences: Mathematics and Physics, Therefore, it is suggested to make a detailed analysis of the topics and sub-topics required in the General Higher Basic Education (EGBS), in order to be able to address them during the career of Pedagogy of the Experimental Sciences: Mathematics and Physics.